Comprehensive Study of Phenotypic and Growth Rate Features of Blastocystis Subtypes 1-3 and 6 in Symptomatic and Asymptomatic Subjects - Karamati, Seyed Ahmad; Mirjalali, Hamed; Niyyati, Maryam; Rezaei Riabi, Tahereh; Yadegar, Abbas; Asadzadeh Aghdaei, Hamid; Haghighi, Ali; Seyyed Tabaei, Seyyed Javad; Zali, Mohammad Reza (Iranian journal of parasitology, 2019)
The present study aimed to assess the grouping of subtypes 1-3 and 6 of according to the size and generation time of the parasite among the symptomatic and asymptomatic subjects. subtypes 1-3 and 6 isolated from symptomatic and asymptomatic subjects and were cultivated in DMEM medium. In order to assess inter- and intra-subtype variation in size, all the isolates were measured using morphometric criteria. Generation time was calculated using approximately 1×10 which were cultivated in DMEM, every 24h for 4 days. All subtypes had 5 to 185 μm diameter range. The smallest size was attributed to ST1, followed by ST6 and ST2. ST3 showed the most variable size and phenotypes compared with the other three subtypes. Furthermore, amoeboid forms and parasite clumping were only seen in ST3-S (symptomatic subjects). Generation time analysis showed that the number of ST1 isolated from symptomatic and asymptomatic subjects peaked higher than the other subtypes. This is the first study discussing inter-intra-size, phenotype and generation time variations among 4 common subtypes of . Accordingly, ST3 was largest subtype and showed most diversities in both size and phenotype, while ST1 was smallest subtype with lowest intra-subtype variation.